2007
DOI: 10.1590/s0100-40422007000400029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acetates in elasmopalpulus lignosellus pheromone glands using a newly created mass spectral database and kóvats retention indices

Abstract: Recebido em 7/6/06; aceito em 6/9/06; publicado na web em 26/3/07Based on a specially created mass spectral database utilizing 23 tetradecenyl and 22 hexadecenyl acetate standards along with Kóvats retention indices obtained on a very polar stationary phase [poly (biscyanopropyl siloxane)] (SP 2340), (Z)-9-hexadecenyl acetate, (Z)-11-hexadecenyl acetate and (E)-8-hexadecenyl acetate were identified in active pheromone extracts of Elasmopalpus lignosellus. This identification was more efficient than our previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Studies of Brazilian populations identified the presence of (E)-8hexadecenyl acetate, (Z)-9-hexadecenyl acetate, and (Z)-11hexadecenyl acetate in the population from Goiânia. Only two acetates which are (Z)-9-hexadecenyl acetate and (Z)-11-hexadecenyl acetate were found in the population from Sete Lagoas, and a mix of two alcohols and three acetates non-identified in the population from Paraná (Jham et al 2005, 2007, de Viana 2015). These differences could be a result of population isolation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Studies of Brazilian populations identified the presence of (E)-8hexadecenyl acetate, (Z)-9-hexadecenyl acetate, and (Z)-11hexadecenyl acetate in the population from Goiânia. Only two acetates which are (Z)-9-hexadecenyl acetate and (Z)-11-hexadecenyl acetate were found in the population from Sete Lagoas, and a mix of two alcohols and three acetates non-identified in the population from Paraná (Jham et al 2005, 2007, de Viana 2015). These differences could be a result of population isolation.…”
Section: Discussionmentioning
confidence: 94%
“…The sex pheromone composition of E. lignosellus of different Brazilian populations from Goiânia (Goias State), Sete Lagoas (Minas Gerais State) (Lynch et al 1984, Jham et al 2005, 2007, and from Paraná State Viana (2015) showed a specific blend of each population. These were also different from North American population, that was described as a mixture of (Z)-7-tetradecenyl acetate, (Z)-9-tetradecenyl acetate, (Z)-9-tetradecenol, and (Z)-11-hexadecenyl acetate (proportion 37:20:4:39) (Lynch et al 1984).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In experiments conducted with different control methods, pest management using pheromone and light traps and soil cover with Crotalaria jucea resulted in a small reduction in the pest population (Jham, Silva, Lima, & Viana, 2007;Gill, McSorley, Goyal, & Webb, 2010). Thus, preventive chemical control and seed treatment remain the most widely used methods to control E. lignosellus.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1980s, efforts have been directed to develop new alternatives based on semiochemicals and natural enemies to control E. lignosellus (Lynch et al, 1984;Pires et al, 1992;Jham et al, 2005Jham et al, , 2007. However, in Brazil, the currently used method is still based on pesticides.…”
Section: Introductionmentioning
confidence: 99%